Quality of life and self-esteem in traffic victims in physical therapy - Marcos Mesquita Filho
Abstract Introduction: Motor vehicles have transformed human life in radical and contradictory ways. At the same time that cars have brought comfort and ease to human life, they are also a main cause of trauma, pain, disability, and death worldwide. Objective: To investigate the quality of life and self-esteem of traffic accident victims undergoing physical rehabilitation. Methods: This was a controlled, cross-sectional study that compared quality of life and self-esteem among traffic accident victims in physical therapy with other accident victims, physical therapy patients for other causes, and the general population. Results: The self-esteem of individuals undergoing physical therapy due to traffic accidents was lower compared to victims of other accidents and those in physical therapy for other reasons (p < 0.05). Regarding quality of life, the study group sample obtained the following mean scores: physical domain 48.1; psychological 52.8; social 68.1; environmental 54.1. These scores were lower than those of traffic accident victims who did not undergo physical therapy and of the general population in all domains (p < 0.05), but higher than that of individuals undergoing physical therapy for other causes, except in the psychological domain. Conclusion: Self-esteem and quality of life were low in traffic accident victims undergoing physical therapy. Physical therapy professionals can play an important role in improving these conditions provided they assume a humanized posture, practicing patient-centered rather than disease-centered health actions.